Hubungan Gaya Kepemimpinan, Stress Kerja Dan Employee Engagement Terhadap Kinerja Pegawai Pada Dinas Pemadam dan Penyelamatan Kabupaten Ogan Komering Ulu - Bela Juliani; Dahlia Dahlia; Yunita Sari (Politeknik Negeri Sriwijaya, 2022)
This study discusses the relationship between leadership style, work stress and employees’ engagement on employees’ performance at the Fire and Rescue Service Oku District. The total population in this study were 43 people. The analytical method used is quantitative method using Multiple Linear Correlation analysis tool. In this study between leadership style (X1), work stress (X2) has a relationship with employees’ performance (Y) with a calculated F value (173.154) > F-table (3.24), then Ho is rejected and Ha is accepted, this means that the variables of Leadership Style, Work Stress and Employees’ Engagement together are significantly related to Employees’ Performance at the Fire and Rescue Service Oku District.